Judicial Pardon: Repositioning Restorative Justice from The Perspective of The National Criminal Code - Hajairin; Syamsuddin; Aman Ma’arij (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Judicial pardon in Article 54 paragraph (2) of the National Criminal Code still has an ambiguous nature and raises concerns about inconsistencies in legal interpretation. This research aims to clarify the principle of insignificance of judicial pardon in the National Criminal Code. The research method is normative legal research focused on examining the application of rules or norms in positive law. The results of this research indicate that, first, there has been a paradigm shift in sentencing post-enactment of the National Criminal Code, moving from imprisonment to restorative justice. Second, it emphasizes the principle of insignificance of Judicial Pardon as a repositioning of Restorative Justice within the perspective of the National Criminal Code by integrating a systematic approach to maintain the coherence of the National Criminal Code, contextual to meet social facts and dynamics, philosophical in the study of Judicial Pardon rooted in restorative justice, and practical guidelines for judges in applying Judicial Pardon. Some judicial pardon decisions post-enactment of the National Criminal Code and National Criminal Procedure Code include the Banjarnegara District Court Decision No. 97/Pid.Sus/2025/PN Bnr in early 2026 regarding Burhani Hasan in a gambling case, the Singaraja District Court Decision No. 1/Pid.C/2026/PN Sgl regarding Rahmat Riandy for petty theft, and the Mempawah District Court Decision No. 512/Pid.B/2025/PN Mpw regarding Hendrikus Bujang in February 2026 for negligence. Third, the synchronization of Judicial Pardon in the Judge's Procedural Guidelines, namely, the judge's pardon needs to consider the provisions of Article 54 paragraphs (1) and (2) of the National Criminal Code Jo. Article 1 number 19 and Article 246 of Law/20/2025/ Criminal Procedure Code as well as SEMA/1/2026/Implementation Guidelines for the 2023 Criminal Code and 2025 Criminal Procedure Code are very necessary to provide formal procedural legitimacy for judges in accommodating justice and humanity.